PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY LEARNING BERBANTUAN AR TERHADAP KEMAMPUAN ANALISIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SD - Rahma Mulyadi Ningrum, Nevita; Mahya Fanny, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The analytical ability of students in IPAS (Integrated Science and Social Studies) learning at the elementary school level is still relatively low. This is due to the use of teacher-centered learning models and the lack of technology-based learning media that can effectively visualize abstract concepts. Therefore, an innovative learning model is needed to actively engage students in meaningful learning experiences. This study aims to determine the effect of the Guided Inquiry Learning model assisted by Augmented Reality on students' analytical skills in IPAS learning for fourth-grade elementary school students. This research employed a quantitative method with a post-test only control group design. The population consisted of all fourth-grade students of SDN Ngagelrejo I/396 Surabaya in the 2025/2026 academic year, totaling 49 students. The sample was selected using cluster random sampling, resulting in two classes: class IV-B as the control group (25 students) and class IV-G as the experimental group (24 students). Data collection was conducted using analytical ability tests in the form of multiple-choice and essay questions. Data analysis techniques included normality test, homogeneity test, and hypothesis testing using the Independent Sample T-Test with SPSS version 26. The results showed that there was a significant effect of the Guided Inquiry Learning model assisted by Augmented Reality on students’ analytical skills. Students in the experimental class demonstrated better analytical abilities compared to those in the control class. Therefore, this learning model can be considered an effective alternative to improve students' analytical skills in IPAS learning at the elementary school level. Keywords: Guided Inquiry Learning, Augmented Reality, Analytical Ability,